2014
DOI: 10.1002/2327-6924.12101
|View full text |Cite
|
Sign up to set email alerts
|

Beyond assessment: Examining providers’ responses to disclosures of violence

Abstract: Purpose Intimate partner violence (IPV) and sexual assault (SA) are significant public health issues. In spite of gains made in research and support for screening, little is known about how healthcare providers respond to disclosures of violence. The purpose of this analysis was to examine providers’ documented responses to women's disclosure of IPV or SA. Data sources This qualitative analysis of healthcare providers’ responses to the disclosure of violence was part of a larger retrospective review of 2000 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…It is essential that NPs become knowledgeable about appropriate counseling services in their area and offer to refer patients (Read et al., ; Sutherland, Fontenot, & Fantasia, ). Currently there are no guidelines for addressing ACE in primary care; however, such a guideline may be useful to NPs as they begin asking about ACE.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential that NPs become knowledgeable about appropriate counseling services in their area and offer to refer patients (Read et al., ; Sutherland, Fontenot, & Fantasia, ). Currently there are no guidelines for addressing ACE in primary care; however, such a guideline may be useful to NPs as they begin asking about ACE.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that FPs recorded a 'code of violence' in only 64% of the IPV cases they encountered, while M/ Ns informed the physician in only 41% of the IPV cases they acknowledged. A study from the United States in 2014 reported that, of physicians who screened patients for IPV, the vast majority (81.5%) did not act appropriately, such as offering a follow-up appointment or making a referral to IPV facilities (Sutherland et al, 2014). In a study reviewing affirmed IPV cases, researchers found that IPV was reported by health institutes in only 31 (9.1%) cases of the 337 records reviewed (Magnussen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Following a positive screen, the clinician has the responsibility to take the following additional actions: 1) complete additional assessments, 2) offer safety planning, and 3) offer referrals . Gathering detailed information through additional assessment to clarify the woman's experience and situation is necessary.…”
Section: Responding To a Positive Screen For Intimate Partner Violencementioning
confidence: 99%
“…Determining timing of the last abusive event and whether sexual violence was involved will direct provision of referrals to sexual assault/forensic nursing services, as the jurisdiction where the assault occurred will have evidence collection time limits, which are usually 72 to 120 hours. There is a strong correlation between IPV and depression, posttraumatic stress, substance use, traumatic brain injury, and reproductive coercion . Thus, screening for depression and substance abuse are also recommended.…”
Section: Responding To a Positive Screen For Intimate Partner Violencementioning
confidence: 99%
See 1 more Smart Citation